2015
DOI: 10.1080/01635581.2015.1055366
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Vitamin C Application in Patients with Radiotherapy-Resistant Bone Metastases: A Retrospective Study

Abstract: The aim of this study was to observe effects of ascorbic acid application on pain, performance status, and survival time in cancer patients. A retrospective cohort of 39 patients with bone metastases treated with radiotherapy was identified. All patients were radiotherapy-resistant. Fifteen patients who received chemotherapy, and 15 patients who received an infusion of 2.5 g ascorbic acid were included in the study. Nine control patients were treated with neither chemotherapy nor vitamin C. Eastern Cooperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 31 publications
0
40
0
1
Order By: Relevance
“…Vitamin B6 works as a coenzyme to transfer amino in amino acid biosynthesis and metabolism. A previous study reported that pain scores in carpal tunnel syndrome patients improved more than other measured parameters following vitamin B6 treatment (Gunes-Bayir & Kiziltan, 2015). Another study reported that circulating vitamin B6 levels were inversely correlated with clinical indicators, including the disability score, duration of morning stiffness and degree of pain, and with biochemical markers, including the erythrocyte sedimentation rate and C reactive protein levels (Chiang et al, 2005).…”
Section: Vitamin B6 Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin B6 works as a coenzyme to transfer amino in amino acid biosynthesis and metabolism. A previous study reported that pain scores in carpal tunnel syndrome patients improved more than other measured parameters following vitamin B6 treatment (Gunes-Bayir & Kiziltan, 2015). Another study reported that circulating vitamin B6 levels were inversely correlated with clinical indicators, including the disability score, duration of morning stiffness and degree of pain, and with biochemical markers, including the erythrocyte sedimentation rate and C reactive protein levels (Chiang et al, 2005).…”
Section: Vitamin B6 Metabolismmentioning
confidence: 99%
“…A previous study showed that intravenous administration of vitamin C relieved pain in patients in comparison to patients who did not receive vitamin C (Gunes-Bayir & Kiziltan, 2015). Vitamin C is easy to consume in pain-derived oxidative stress, and it is a sensitive indicator of the initiation of pain.…”
Section: Ascorbic Acid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Cameron and Campbell [81] reported a number of cases of dramatic to complete amelioration of bone pain in patients with severe cancer-related pain given both high dose oral and intravenous vitamin C (Table 3). Retrospective studies of patients with bone metastases receiving 2.5 g intravenous vitamin C once weekly or during intensifying pain reported a range of responses, including 0–100% decreases in pain [83, 84]. These, and the earlier case studies [81], indicate that vitamin C can potentially provide dramatic improvements in pain relief in cancer patients with bone metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies of patients with bone metastases receiving 2.5 g intravenous vitamin C once weekly or during intensifying pain reported a range of responses, including 0–100% decreases in pain [83, 84]. These, and the earlier case studies [81], indicate that vitamin C can potentially provide dramatic improvements in pain relief in cancer patients with bone metastases.…”
Section: Introductionmentioning
confidence: 99%